1595. Ceftobiprole Activity against Gram-Positive Pathogens Causing Bone and Joint Infections in the United States from 2016 through 2019. (31st December 2020) - Duncan, Leonard R; Hamed, Kamal; Smart, Jennifer; Pfaller, Michael A; Flamm, Robert K; Mendes, Rodrigo E
Abstract: Background: Bone and joint infections (BJIs) cause serious morbidity and mortality and present significant treatment challenges. Ceftobiprole medocaril, the prodrug of ceftobiprole, is an advanced cephalosporin approved in many European and non-European countries for the treatment of adults with community- and hospital-acquired pneumonia, excluding ventilator-associated pneumonia. Ceftobiprole medocaril is not approved in the United States (USA) but has qualified infectious disease product (QIDP) status, and is being evaluated in two phase 3 clinical trials in patients with acute bacterial skin and skin structure infections (completed) or Staphylococcus aureus bacteremia (ongoing). In this study, the activity of ceftobiprole and comparators was evaluated against recent Gram-positive clinical isolates collected from BJIs in the USA. Methods: 306 Gram-positive pathogens were collected from patients with BJIs at 27 US medical centers from 2016 through 2019. Susceptibility to ceftobiprole and comparator agents was tested using current CLSI methods. CLSI and EUCAST interpretive criteria were applied according to current guidelines. Results: The major Gram-positive species and pathogen groups included S. aureus (67.0%; methicillin-resistant S. aureus [MRSA], 35.1%), β-hemolytic streptococci (BHS; 13.7%), coagulase-negative staphylococci (CoNS; 9.5%), and Enterococcus faecalis (6.9%). Ceftobiprole was highly active against S. aureus (MIC50/90 values, 0.5/1 mg/L; 100.0% susceptible by EUCAST criteria), including MRSA (MIC50/90 values, 1/2 mg/L). Ceftobiprole also exhibited potent activity against other Gram-positive cocci, including BHS (MIC50/90 values, 0.015/0.03 mg/L; 100% inhibited at ≤ 4 mg/L, which is the EUCAST PK-PD non-species-related breakpoint), CoNS (MIC50/90 values, 1/4 mg/L; 100% inhibited at ≤4 mg/L), and E. faecalis (MIC50/90 values, 0.5/2 mg/L; 100.0% inhibited at ≤ 4 mg/L). Conclusion: Ceftobiprole was highly active against clinical BJI isolates from the major Gram-positive pathogen groups collected at US medical centers during 2016–2019. The broad-spectrum activity of ceftobiprole, including potent activity against MRSA, supports its further evaluation for this potential indication. Disclosures: Leonard R. Duncan, PhD, A. Menarini Industrie Farmaceutiche Riunite S.R.L. (Research Grant or Support)Basilea Pharmaceutica International, Ltd. (Research Grant or Support)Dept of Health and Human Services (Research Grant or Support) Kamal Hamed, n/a, Basilea Pharmaceutica International Ltd. (Employee) Jennifer Smart, PhD, Basilea Pharmaceutica International, Ltd (Employee)Department of Health and Human Services (Research Grant or Support) Michael A. Pfaller, MD, Amplyx Pharmaceuticals (Research Grant or Support)Basilea Pharmaceutica International, Ltd (Research Grant or Support)Cidara Therapeutics (Research Grant or Support)Cidara Therapeutics (Research Grant or Support)Department of Health and Human Services (Research Grant or Support)Fox Chase Chemical Diversity Center (Research Grant or Support)Paratek Pharma, LLC (Research Grant or Support) Robert K. Flamm, PhD, A. Menarini Industrie Farmaceutiche Riunite S.R.L. (Research Grant or Support)Amplyx Pharmaceuticals (Research Grant or Support)Basilea Pharmaceutica International, Ltd (Research Grant or Support)Department of Health and Human Services (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support) Rodrigo E. Mendes, PhD, A. Menarini Industrie Farmaceutiche Riunite S.R.L. (Research Grant or Support)Allergan (Research Grant or Support)Allergan (Research Grant or Support)Basilea Pharmaceutica International, Ltd (Research Grant or Support)Cipla Ltd. (Research Grant or Support)Department of Health and Human Services (Research Grant or Support)GlaxoSmithKline (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Merck (Research Grant or Support)Merck (Research Grant or Support)Pfizer (Research Grant or Support)